From 'mission-shaped' to 'Jesus-shaped' church: hospitality as a missiological agenda in the Church of England - Cross, Susan Beverley (Anglican-Episcopal theology and history, 2025)
"Hospitality is often invoked without question in Church of England discourse, but the importance of the practice to contemporary mission has not been subject to detailed analysis. This book provides otherwise elusive in-depth theological examination of the scope of Christian understandings of hospitality. From feasting in the Hebrew Scriptures, and foot-washing in the New Testament, to online Communion during the COVID-19 pandemic, hospitality is more than 'welcome', or the evangelistic hospitality of the Alpha Course or Messy Church. So this book encompasses racism, ageing, poverty, tragedy, storytelling, minds, bodies and belonging, as well as the implications of allying food to Christian formation. It shows that Christian hospitality has relevance not only to mission, but also to ecclesiology, eschatology, disability theology, and social and ecological justice"--